Kleči prevajanja evropske pravne terminologije - Mišič, Luka (Podjetje in delo, 2021)
The article is a result of the author's several years of experience in drafting the dictionary on European legal terminology that is still in preparation. The English-Slovenian terminological dictionary, aimed at transposing European legal terminology into the Slovenian legal environment, is prepared under a joint research venture by the Faculty of Law at the University of Ljubljana and the Fran Ramovš Institute of the Slovenian Language at the Research Centre of the Slovenian Academy of Sciences and Arts. The research is financed by the Slovenian Research Agency (under Programme No. P5-0217). The article addresses several challenges faced over the years by the so-called terminology group of the Ljubljana law school, mainly concerning literal and descriptive translations of terms in English, the attribution of domestic or other distinct meanings to particular notions inherent to particular legal orders, or, for example, overwhelming reliance on already existing but possibly ill-considered terminological agreements. Such and other challenges, like the creation of European legal terminology based solely on Euro-English, even if the latter is excluded from this debate, might also appear in everyday practice of lawyers and other professionals, especially those bound by strict time constraints regarding their translations. The aim of this paper is to draw attention to these and other similar issues, and with some luck contribute to uniform and substantively appropriate translation practices even before the publication of the said dictionary.
Keywords: angleščina; dictionary; English; EU law; European law; evropsko pravo; legal terminology; pravna terminologija; pravni slovarji; pravo Evropske unije; prevodi; slovarji; Slovene; slovenščina; translation